Memorial acadêmico: uma reflexão sobre minha prática pedagógica - OLIVEIRA, Mirian do Socorro Santos de (2023)
This research it is result from one process of growth and professitional maturation and personal and the conclucion of the course of Pedagogy form Universidade Federal do Pará, UFPA/PARFOR. The research was made of the qualitative and bibiography it is one memorial, tha talks from may formation and teaching pratice. Through it I remembered my pratice looking for always support me in thinkes like: Miguel Arroyo, Maria Lucia Arruda Aranha, Vera Maria Candau, Paulo Freire and others. To show more my experiences and my relationship with university I divede my memorial in thrre parts.The capter One fom memorial talks about my personal history and my difficulties. The second capter tlaks about my formations im Magistery and my experiences. In the third capter iwill talk about my academic formation, the klowdlegies during the Pedagogy course and the contribution from the course for my pratical life that were very important. The incumbency of write about my trajectory like teacher took along me until one dificult action to remembered and reflections about me and my teaching pratice.